Buccal swabs as non-invasive specimens for detection of severe acute respiratory syndrome coronavirus-2. Issue 5 (May 2021) - Gaur, Ritu; Verma, Dipesh Kumar; Mohindra, Ritin; Goyal, Kapil; Gupta, Shipra; Singla, Vidhi; Sahni, Vaibhav; Ghosh, Arnab; Soni, Roop Kishor; Bhalla, Ashish; Gauba, Krishan; Singh, Mini P.
Introduction: The current gold standard for detection of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) RNA involves subjecting nasopharyngeal or oropharyngeal swabs to reverse transcription quantitative PCR (RT-qPCR). However, both sample types need to be collected by trained professionals. Using self-collected buccal swabs as an alternative could simplify and accelerate diagnosis of coronavirus disease 2019 (COVID-19). Objective: To assess self-collected buccal swab samples as an alternative method for SARS-CoV-2 detection in patients with COVID-19. Methods: Buccal swab samples were self-collected by 73 patients with COVID-19. Total RNA was extracted using Qiagen kits. RNA encoding the SARS-CoV-2 Env protein and human RNase P as an internal control was amplified using the TRUPCR ® SARS-CoV-2 RT-qPCR kit version 2.1 and a Bio-Rad CFX96 Real-Time Detection System. Result: The sensitivity of RT-qPCR from buccal swabs was 58.9% (43/73; 95% confidence interval [CI] 46.77%–70.27%) and that of RT-qPCR from saliva was 62.90% (39/62; 95% CI 49.69%–74.84%) taking positive SARS-CoV-2 RT-qPCR from nasopharyngeal swabs as the gold standard. Conclusion: Self-collected buccal swabs are promising alternatives to nasopharyngeal or oropharyngeal swabs for SARS CoV-2 detection.